ANALISIS TIME SERIES DAN CROSS SECTION PERBANDINGAN KINERJA KEUANGAN 3 PERUSAHAAN MANUFAKTUR - Adam Permana Putra; Mufidah Sahla Oktavianty; Nur Aini Qurrata A’yun (Trending: Jurnal Manajemen dan Ekonomi, 2023)
This study aims to determine the financial performance of manufacturing companies for the 2019-2021 period using financial ratios. The research results show that: PT. Kabelindo Murni, PT. Astra International Tbk, and PT. Indomobil Sukses Tbk for the 2019 -2021 period relies on accounting for the weight of assessing financial aspects based on the Decree of the Minister of State-Owned Enterprises Number: Kep-100/MBU/2002. Based on the research, the results of financial ratio analysis of PT. Kabelindo Murni, PT. Astra International Tbk, and PT. Indomobil Sukses Tbk for the 2019 -2021 period shows the results of Liquidity Ratios, Activity Ratios, Solvency Ratios, and Profitability Ratios.